Typology of Orthographic Interference: Linguistic Foundations for Improving the National Writing System - Amirzhanova, Nazira; Soltanbekova, Alfiya; Urkinbayev, Serik; Ramazanov, Talgat; Sadyk, Ainagul; Zhunusova, Marina (Forum for Linguistic Studies, 2025)
The article explores orthographic interference in the process of improving the normative tools of national writing. Orthographic interference is a linguistic phenomenon that arises from the interaction of different language systems, manifesting as deviations or violations of writing norms. The study analyzes changes and adaptations of linguistic norms and their impact on the writing skills of language learners. It focuses on identifying linguistic mechanisms to improve the national writing system by preventing and reducing orthographic interference. The study employs content analysis, comparative methods, and qualitative analysis. Over 60 students’ written works were examined to determine the frequency, typology, and causes of orthographic errors. The analysis identified common types of interlingual and intralingual interference. Interlingual interference results from the influence of Russian and English graphic, phonological, and morphological features, while intralingual interference arises from inadequate understanding of the phonetic and phonological foundations of the language. Content analysis identified the most frequent orthographic errors, with primary causes including insufficient mastery of spelling rules, differences between native and target language writing systems, and teaching method shortcomings. These errors serve as indicators of students’writing experience and language proficiency. The identified types of interference contribute to improving normative tools, assessing the effectiveness of educational programs and methodologies, standardizing orthographic norms, and enhancing writing culture in multilingual societies. The findings support the codification of Kazakh orthographic norms and the development of a scientific and methodological foundation for reducing linguistic interference.